Pharmaceutical care for symptoms of allergy during pregnancy and lactation: rational choice and use of antihistamines - T. B. Ryvak; O. M. Nepyivoda; A. Ya. Koval (Zaporožskij Medicinskij Žurnal)
The aim of this study was to conduct a clinical-pharmaceutical evaluation of the rational choice and use of antihistamines during pregnancy and lactation by questionnaire survey.